PELAKSANAAN TUGAS BADAN PENGAWAS OBAT DAN MAKANAN (BPOM) DALAM PENGAWASAN PANGAN YANG MENGANDUNG BAHAN BERBAHAYA DI KOTA PEKANBARU - Simarmata, Jumpa Malum; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Government regulates consumer protection explicitly in Act Number 8 of 1999 on Consumer Protection. The problem formulation of this thesis: First, the implementation of the tasks of Food and Drug Supervisory Agency in monitoring food containing harmful ingredients in Pekanbaru, Second, barriers to the implementation of the tasks of Food and Drug Supervisory Agency in monitoring food containing harmful ingredients in Pekanbaru.In this study, the authors use a kind of sociological research the nature of descriptive research that accurately describe the nature of an individual, phenomenon, studied. This research was conducted in BPOM Pekanbaru, while population and sample an entire party related to the problem under study, data collection techniques interview with the head section of the examination, questionnaire data collection methods make a list of questions that have a correlation with the problems studied by the author to consumers and businesses, namely data collection study literature library reading literature, qualitative data analysis is based on the description of sentences and draw conclusions deductively that from the general to the particular, the date source used, primary date, secondary and tertiary.The results obtained from this study, first, the implementation of the tasks BPOM Pekanbaru refers to the Minister of Trade Regulation Number 44 Year 2009 concerning Procurement, Distribution and Monitoring of Hazardous Materials. Second, barriers, industries that use harmful ingredients not listed on Industry and Trade and the Department of Health, the people's habits, lack of human resources BPOM Pekanbaru.Based on the research results, there are two basic problems that can be inferred. First, the implementation of the tasks BPOM Pekanbaru refers to the Minister of Trade Regulation Number 44 Year 2009 concerning Procurement, Distribution and Monitoring of Hazardous Materials. Second, barriers, lack of implementation of duties and functions, because the vast working area, the lack of human resources. Suggestions author, first, to optimize the duties and functions of BPOM Pekanbaru by increasing human resources. Second, the industry must have a permit, people's habits have to be changed.Keywords: Implementation - Consumer Protection - Food - Hazardous Materia